Erythropoietin Improves Signaling through Tyrosine Phosphorylation in Platelets from Uremic Patients - Diaz-Ricart, Maribel; Estebanell, Eva; Cases, Aleix; López-Pedret, José; Castillo, Ricardo; Ordinas, Antonio; Escolar, Ginés (Thrombosis and Haemostasis, 1999)
Erythropoietin has shown to be effective in the correction of the hemostatic defect present in uremic patients. We have investigated the possible effect of recombinant human erythropoietin (rHuEPO) on the signaling processes occurring in platelets. Platelet suspensions were obtained from hemodialyzed patients before and after at least one month of initiating treatment with rHuEPO. Aliquots of non-activated or thrombin-activated platelets were treated to obtain platelet lysates or processed to extract platelet cytoskeleton. Samples were resolved by 8% SDS-polyacrylamide gel electrophoresis followed by Western blotting. After thrombin activation, proteins p120, p85, p78, p75, pp62, pp60, p59, p58, p56, p54 and p52 associated with the Triton-insoluble cytoskeletal fraction appeared phosphorylated in control profiles. In profiles from platelets obtained from uremic patients before treatment with rHuEPO, only proteins p58 and p56 appeared clearly and p54 was slightly phosphorylated. However, in platelets from the same patients under rHuEPO treatment, thrombin-induced phosphorylation improved to levels even above those observed in control profiles. Specially, the band at 54KDa appeared consistently more phosphorylated in all the patients under rHuEPO treatment. Although it is accepted that part of the hemostatic effect of erythropoietin is mediated by an increase in hematocrit, our study suggests that it enhances platelet signaling in uremic platelets which may explain the improvement of platelet response to activating stimulus before clinically noticeable elevation of hematocrit.Abbrevations: rHuEPO = recombinant human erythropoietin; SDS-PAGE = sodium dodecyl sulphate-polyacrylamide gel electrophoresis; CPD = citrate/phosphate/dextrose; PRP = platelet-rich plasma; HBSS = Hanks’ balanced salt solution; EGTA = ethylene glycol bis (β-aminoethylether)-N,N,N’,N’-tetraacetic acid; EDTA = ethylenediaminetetraacetic acid, PMSF = phenylmethylsulphonyl fluoride, ECL = enhanced chemiluminiscence